2020
DOI: 10.3390/biom10121659
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of the PTPN13 Tyrosine Phosphatase in Cancer

Abstract: In this review article, we present the current knowledge on PTPN13, a class I non-receptor protein tyrosine phosphatase identified in 1994. We focus particularly on its role in cancer, where PTPN13 acts as an oncogenic protein and also a tumor suppressor. To try to understand these apparent contradictory functions, we discuss PTPN13 implication in the FAS and oncogenic tyrosine kinase signaling pathways and in the associated biological activities, as well as its post-transcriptional and epigenetic regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 146 publications
1
20
0
Order By: Relevance
“…S3E). PTPN13 has been shown to be involved in multiple signaling pathways including dephosphorylation of IRS-1 and inhibition of PI3K (16). By comparison, category IIB consisted of 340 phosphosites on 248 proteins that were up-regulated by ligand in IGF1Rexpressing cells significantly greater than in IR-expressing cells.…”
Section: Differential Phosphorylated Patterns By Ir and Igf1r In Ligandmentioning
confidence: 99%
“…S3E). PTPN13 has been shown to be involved in multiple signaling pathways including dephosphorylation of IRS-1 and inhibition of PI3K (16). By comparison, category IIB consisted of 340 phosphosites on 248 proteins that were up-regulated by ligand in IGF1Rexpressing cells significantly greater than in IR-expressing cells.…”
Section: Differential Phosphorylated Patterns By Ir and Igf1r In Ligandmentioning
confidence: 99%
“…The previous article studied the role of PTPN13 in FAS-mediated apoptosis. The interaction of PTPN13 and the FAS (CD95/APO-1) death receptor is reported as the first evidence ( 52 ). In our report, the results showed that PTPN13 expression in normal tissues is lower than that in PAAD tissues, but PTPN13 expression in PAAD patients has nothing related to the tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…PTPN13 is a tyrosine phosphatase that is frequently downregulated or silenced in several tumors. In addition, it is thought to be an independent prognostic marker for increased overall survival in several cancers [ 54 ]. Further evidence demonstrated that PTPN13 overexpression inhibited cell invasiveness through cell junction stabilization [ 55 ].…”
Section: Discussionmentioning
confidence: 99%